ZBP1 and heatstroke - Li, Fanglin; Deng, Jiayi; He, Qiuli; Zhong, Yanjun (Frontiers in Immunology, 2023)
Abstract: Associated with circulatory failure and multiorgan dysfunction, heatstroke is a heat-stress induced, life-threatening condition characterized by a raised core body temperature and central nervous system dysfunction. As global warming continues to worsen, heatstroke is expected to become the leading cause of death globally. Despite the severity of the condition, the detailed mechanisms that underlie the pathogenesis of heatstroke still remain largely unknown. Z-DNA-binding protein 1 (ZBP1), also referred to as DNA-dependent activator of IFN-regulatory factors (DAI) and DLM-1, was initially identified as a tumor-associated and interferon (IFN)-inducible protein, and was recently reported to be a Z–nucleic acid sensor that regulates cell death and inflammation; however, the biological function has not yet been fully understood. In the present study, a brief review of the main regulators is presented, in which the Z–nucleic acid sensor ZBP1 was identified to be a significant factor in regulating the pathologic characteristics of heatstroke through ZBP1-dependent signaling. Thus, the lethal mechanism of heatstroke was revealed, in addition to a second function of ZBP1 other than as a nucleic acid sensor.